Benign prolapsing inflammatory rectal polyp with osseous metaplasia mimicking rhabdomyosarcoma botryioides - A.A. Amir; K.A. Nouli; S.S. Sheikh (Elsevier, 2020)
Introduction: We herein report a rare case of rectal inflammatory polyp with osseous metaplasia that interestingly presented as a prolapsed mass clinically mimicking rhabdomyosarcoma botryioides. Presentation of case: The patient is a 10 year-old male with a protruding mass through the anus, which in children, usually raises immediate suspicion of a botryioides tumor. Whilst the mass in this case did indeed mimic malignancy in the form of rhabdomyosarcoma botryioides, it was proved to be a benign entity in the form of an inflammatory rectal polyp containing osseous metaplasia. The polyp measured in at 95 mm, making it the largest documented case of osseous metaplasia in a benign colorectal polyp. Discussion: Regarding the formation of osseous metaplasia, it is hypothesized that mature fibroblasts within some intestinal lesions may be exposed to transcription which could result in the generation of induced pluripotent stem cells capable of differentiating into osteoblasts, ultimately producing the metaplastic bony formations. Other theories are available, however. Conclusion: Osseous metaplasia is rarely detected in the gastrointestinal tract with most cases reported in malignant lesions and only a few in benign polyps. It is also important to raise awareness of this clinical mimic of sarcoma for clinicians and pathologists to properly diagnose and treat such cases. Keywords: Rhabdomyosarcoma botryioides, Inflammatory polyp, Osseous metaplasia